The Epigenetic Regulation of Microenvironment in Hepatocellular Carcinoma - Wang, Fang; Malnassy, Greg; Qiu, Wei (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is a highly lethal and complex malignancy strongly influenced by the surrounding tumor microenvironment. The HCC microenvironment comprises hepatic stellate cells (HSCs), tumor-associated macrophages (TAMs), stromal and endothelial cells, and the underlying extracellular matrix (ECM). Emerging evidence demonstrates that epigenetic regulation plays a crucial role in altering numerous components of the HCC tumor microenvironment. In this review, we summarize the current understanding of the mechanisms of epigenetic regulation of the microenvironment in HCC. We review recent studies demonstrating how specific epigenetic mechanisms (DNA methylation, histone regulation, and non-coding RNAs mediated regulation) in HSCs, TAMs, and ECM, and how they contribute to HCC development, so as to gain new insights into the treatment of HCC via regulating epigenetic regulation in the tumor microenvironment.